Unintentional firearm deaths among children, 0–17 years of age, by race: Findings from the national violent death reporting system, 2015–2021 - Samuel Fischer; Matthew Miller; Eliot W. Nelson; Christopher Chang; Deborah Azrael (Injury Epidemiology)
Abstract Background Unintentional firearm death (UFD) rates are higher among Black children than among White and Hispanic children. Whether disparities in UFD rates among Black as compared to White and Hispanic children vary by other demographic characteristics or by circumstances is unknown. Methods Data come from the 32 states contributing to the National Violent Death Reporting System (NVDRS), 2015–2021. Our sample comprises children 0–17 who died from unintentional firearm injuries. Race/ethnicity- and age-specific population data at the state and county level were used to calculate rates. UFD rates were compared within and across race-ethnicity groupings by age, sex, urbanization and across four NVDRS coded circumstances. Urbanization was assigned using a six-level urban–rural classification scheme from the National Center for Health Statistics (NCHS) based on the county in which the fatal injury occured. Findings Of the 568 UFDs, four-fifths of victims were male (82%) and four-fifths died in a home (84%), usually the Victim’s home (55%). Most deaths involved a child playing with a firearm (63%). Overall, UFD rates were 4.6-fold higher for Black children compared with White children. Black children’s rates were more than 6-fold higher than those of White children for females and for children five to nine years of age, and nearly 8-fold higher for children living in large central metro counties. Conclusions Black children die from unintentional firearm injury at disproportionately high rates, especially young children living in urban centers. The underlying reasons for these racial disparities are unclear and should be a priority for future research.